Inclusion in practice: the importance of resources room and specialized educational service (Research, Society and Development, 2020)
Brazil is not yet a country of reference when it comes to inclusive education, but it is making great strides towards this and as educational institutions, increasingly, developing studies and actions on this theme. As a way of contributing to this theme, interviews were conducted with 237 teachers, parents and guardians of students from different locations and with 20 students from a public school located in the city of Itapecerica da Serra, in São Paulo. The main objective of this study was to understand the advantages of using the resource room and the Specialized Educational Service combined with regular education for effective and inclusive learning in basic education. This qualitative research makes it possible to perceive the same great part of the teachers and responsible for students who know or who are a student with a disability, not everyone knows or knows how a Multifunctional Resource Room works and how it is done by the Educational Service Skilled. This reflects that discussions on this topic are of great relevance. To conclude that the objective of this study was achieved, as the following results could reflect and understand the importance of including students with special requirements and how it is carried out in practice.